Constructions with Reflexive and Reciprocal Verbs in English and Armenian - Mkhitaryan, Yelena; Vardanyan, Mary (Armenian Folia Anglistika, 2014)
Reflexive and reciprocal verbs constitute a special class both in the English and Armenian verbal system. As for their semantics, they manifest similarity, but morphologically and syntactically they show some differences. In English the meanings of reflexivity and reciprocity are expressed both by single verbs and their combination with the respective pronouns. In Armenian these categories are designated by means of the suffix վ. The English reflexives may be used with the pronouns without apparent semantic change, whereas the Armenian counterparts normally do not take them. Used with other words than the respective pronouns these verbs lose the meanings of reflexivity and reciprocity and function as common transitive verbs.